Effect of the potassium serhat application on the microbiological quality of poultry meats during the cold storage - Ahmet Güner; Yusuf Doğruer; Gürkan Uçar; Abdullah Keleş (Eurasian Journal of Veterinary Sciences)
Efect of the potassium sorbate on the microbiological quality of different pouttry species (partridge, quail, turkey, chicken) dipped into potassium sorbate solution (0%, 2.5%, 5%) during the cold storage was investigated. It was determined that potassium sorbate application was very effective on total mesophilic aerobic, total psychrophylic aerobic, coliform, Enterobacteriaceae, Micrococcus-Staphylococcus and mould-yeast in each of the poultry species at the different stage of the storage, In conclusion, whearas two levels of potassium sorbate application was found to be effective in quail and patridge meal, 5% application was in the turkey and chicken meat. And also 5% application is suitable for long time storage.